TELAAH MAQASID SYARIAH TERHADAP LEGALITAS PERJANJIAN PRANIKAH: PROTEKSI PREVENTIF DALAM HUKUM MODERN - Firmansyah, Firmansyah (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2025)
A prenuptial agreement is a legal instrument aimed at protecting individual rights within marriage, particularly in addressing potential issues that may arise in the future. From the perspective of modern law, this agreement is seen as a form of preventive protection for the rights of spouses, especially concerning shared property and other rights. This study aims to analyze the legality of prenuptial agreements from the perspective of maqasid syariah, focusing on the preventive protection provided for individuals and families. The research method used is a qualitative library approach, analyzing various Islamic and positive law literatures. The results of the study show that prenuptial agreements can be considered valid and legal in Islamic law if they meet the principles of maqasid syariah, such as protecting individual rights, justice, and the common good. Furthermore, prenuptial agreements can be an effective preventive tool in avoiding future disputes, thus providing legal certainty and protecting family harmony.